Denser and greener cities: Green interventions to achieve both urban density and nature. Issue 1 (11th January 2023) - McDonald, Robert I.; Aronson, Myla F. J.; Beatley, Timothy; Beller, Erin; Bazo, Micaela; Grossinger, Robin; Jessup, Kelsey; Mansur, Andressa V.; Puppim de Oliveira, José Antonio; Panlasigui, Stephanie; Burg, Joe; Pevzner, Nicholas; et al.
Abstract: Green spaces in urban areas—like remnant habitat, parks, constructed wetlands, and street trees—supply multiple benefits. Many studies show green spaces in and near urban areas play important roles harbouring biodiversity and promoting human well‐being. On the other hand, evidence suggests that greater human population density enables compact, low‐carbon cities that spare habitat conversion at the fringes of expanding urban areas, while also allowing more walkable and livable cities. How then can urban areas have abundant green spaces as well as density? In this paper, we review the empirical evidence for the relationships between urban density, nature, and sustainability. We also present a quantitative analysis of data on urban tree canopy cover and open space for United States large urbanized areas, as well as an analysis of non‐US Functional Urban Areas in OECD countries. We found that there is a negative correlation between population density and these green spaces. For Functional Urban Areas in the OECD, a 10% increase in density is associated with a 2.9% decline in tree cover. We argue that there are competing trade‐offs between the benefits of density for sustainability and the benefits of nature for human well‐being. Planners must decide an appropriate density by choosing where to be on this trade‐off curve, taking into account city‐specific urban planning goals and context. However, while the negative correlation between population density and tree cover is modest at the level of US urbanized areas ( R 2  = 0.22), it is weak at the US Census block level ( R 2  = 0.05), showing that there are significant brightspots, neighbourhoods that manage to have more tree canopy than would be expected based upon their level of density. We then describe techniques for how urban planners and designers can create more brightspots, identifying a typology of urban forms and listing green interventions appropriate for each form. We also analyse policies that enable these green interventions illustrating them with the case studies of Curitiba and Singapore. We conclude that while there are tensions between density and urban green spaces, an urban world that is both green and dense is possible, if society chooses to take advantage of the available green interventions and create it. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.